2005
DOI: 10.1159/000087374
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung körperlicher Aktivität bei Anorexia nervosa: Dimensionen, Erfassung und Behandlungsstrategien aus Expertensicht

Abstract: Zielsetzung: Übersteigerte körperliche Aktivität ist ein zentrales Merkmal der Anorexia nervosa (AN). Dennoch wurde diesem Aspekt der Essstörung bisher in der Forschung wenig Beachtung geschenkt. Daher wurden in der vorliegenden Untersuchung internationale klinische Experten aus dem Bereich der Essstörungen zur Bedeutsamkeit verschiedener Dimensionen körperlicher Aktivität (z.B. exzessives Sporttreiben, pathologische und zwanghafte Einstellungen zum Sport) bei AN-PatientInnen befragt. Darüber hinaus wurden die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the 1980s and 1990s, first treatment approaches applied response prevention techniques including one hour of supervised bed rest after meals to reduce compulsive exercise behavior [ 39 ]. A 2005 review by Hechler and colleagues [ 40 ] showed that unstructured psycho-education, self-monitoring of daily physical activity and cognitive restructuring were the most frequently used treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s and 1990s, first treatment approaches applied response prevention techniques including one hour of supervised bed rest after meals to reduce compulsive exercise behavior [ 39 ]. A 2005 review by Hechler and colleagues [ 40 ] showed that unstructured psycho-education, self-monitoring of daily physical activity and cognitive restructuring were the most frequently used treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…228,229 In relation to treatment outcomes, commitment to exercise is a problem in inpatients and engagement in excessive sport in outpatients may be a barrier to treatment. 230 In addition, high PA may arise prior to illness 231,232 and remain following recovery. 225,233 Therefore, excessive exercise behaviours may also contribute to the aetiology of AN rather than simply being a symptom of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…232,[234][235][236][237] Recently, a study reported increased PA in a subgroup of AN patients only, suggesting that high PA may not be universal in this patient group. 238 The hypothesised drivers of increased PA in AN are cognitive desire to lose weight, 225 to improve mood 230 and to reduce anxiety. 239,240 This is supported by the fact that women with AN are reported to value negative affect regulation as a motivator for exercise more than they value exercising to improve health and fitness.…”
Section: Introductionmentioning
confidence: 99%